Evaluación del 10% de hierbabuena (Mentha sativa) en la alimentación de cobayos (Cavia porcellus) en la parroquia Eloy Alfaro, barrio Santa Rosa de Pichul - Obando Orosco, Myriam Elizabeth (2015)
This research was conducted in the Cotopaxi province, Latacunga Canton, Eloy Alfaro parish, Santa Rosa de Pichul neighborhood; the main objective was to evaluate 10% of hierba buena in the cobayos feeding in order to determine their influence on the production parameters, and the variables were evaluated: weight gain, feed conversion, food consumption, morbidity and mortality and production costs. The Student t test was used to determine the results of the experiment, so the treatments were identified as: control treatment (T0) only fed with alfalfa and Treatment 1 (T1) fed with alfalfa plus 10% of peppermint, which it was administered daily before providing alfalfa; for research were used cobayos males weaned....